Warmest congratulations on your achievement !!! / Wan Noorli Razali - Razali, Wan Noorli (Academy of Language Studies, 2021)
Two APB lecturers have been promoted to the rank of Associate Professor (DM54) recently. Our heartiest congratulations to Assoc. Prof. Dr. Che Rushita Ismail and Assoc. Prof. Dr. Mah Boon Yih who were promoted on 28 May 2021 and 16 July 2021 respectively. It is hoped that this meaningful promotion will encourage them to take on new challenges and grow professionally for themselves, the department, and the university.